Malaysian Indians and Education : Reimagined Development Opportunities - Nagappan, Rajendran; Mukherjee, Hena (Routledge critical studies in Asian education, 2023)
"This edited volume provides a comprehensive overview and discussion of the issues surrounding the Malaysian Indian community's educational development. Malaysian Indian citizens who make up seven per cent of the population have their own set of strengths and weaknesses, while facing deep-seated socio-economic challenges. Education is seen as an enabler which could significantly facilitate social and economic upward mobility, as shown in policies and practices implemented under the New Economic Policy, many of which have unfortunately bypassed the Indian Community. This book explores and assesses the various aspects of the education endeavour of Malaysian Indians, including primary, secondary, post-secondary and tertiary education. Related challenges include urban poverty, school dropouts, dysfunctional families, and other socio-economic issues. It reconsiders educational equity policies and practices in place while proposing new initiatives which could support and chart a way forward for the development of Malaysian Indians. Importantly, the publication addresses the roles of the government, private sector and civil society to help elevate the educational achievements of the Indian Community. The book will appeal to students and academics in the faculties of social science and comparative education, development economics, and sociology, with a focus on access and equity in education. Proposals for change would be of interest to policy-makers and managers of educational and non-governmental organisations in plural societies"--